Demineralized Bone Matrix to Augment Tendon-Bone Healing: A Systematic Review. Issue 10 (24th October 2017) - Hexter, Adam T.; Pendegrass, Catherine; Haddad, Fares; Blunn, Gordon
Background: Following injury to the rotator cuff and anterior cruciate ligament, a direct enthesis is not regenerated, and healing occurs with biomechanically inferior fibrous tissue. Demineralized bone matrix (DBM) is a collagen scaffold that contains growth factors and is a promising biological material for tendon and ligament repair because it can regenerate a direct fibrocartilaginous insertion via endochondral ossification. Purpose: To provide a comprehensive review of the literature investigating the use of DBM to augment tendon-bone healing in tendon repair and anterior cruciate ligament reconstruction (ACLR). Study Design: Systematic review. Methods: Electronic databases (MEDLINE and EMBASE) were searched for preclinical and clinical studies that evaluated the use of DBM in tendon repair and ACLR. Search terms included the following: ("demineralized bone matrix" OR "demineralized cortical bone") AND ("tissue scaffold" OR "tissue engineering" OR "ligament" OR "tendon" OR "anterior cruciate ligament" OR "rotator cuff"). Peer-reviewed articles written in English were included, and no date restriction was applied (searches performed February 10, 2017). Methodological quality was assessed with peer-reviewed scoring criteria. Results: The search strategy identified 339 articles. After removal of duplicates and screening according to inclusion criteria, 8 studies were included for full review (tendon repair, n = 4; ACLR, n = 4). No human clinical studies were identified. All 8 studies were preclinical animal studies with good methodological quality. Five studies compared DBM augmentation with non-DBM controls, of which 4 (80%) reported positive findings in terms of histological and biomechanical outcomes. Conclusion: Preclinical evidence indicates that DBM can improve tendon-bone healing, although clinical studies are lacking. A range of animal models of tendon repair and ACLR showed that DBM can re-create a direct fibrocartilaginous enthesis, although the animal models are not without limitations. Before clinical trials are justified, research is required that determines the best source of DBM (allogenic vs xenogenic) and the best form of DBM (demineralized cortical bone vs DBM paste) to be used in them.